2017
DOI: 10.1097/mao.0000000000001505
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Preoperative Steroids in Atraumatic Cochlear Implantation Surgery

Abstract: Cochlear trauma influenced postimplantation hearing loss and steroid effect on fibrosis. Fibrosis, and to a lesser extent, postimplantation hearing loss increased proportionally to the depth of insertion. Steroids did not influence fibrosis relating to the cochleostomy, but could reduce scarring as the electrode negotiated the hook region or near the electrode tip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…In the 1990s and into this century, the first steps toward "soft surgery" in cochlear implantation began to be implemented (6,11,12). Now the use of soft electrodes, a round window approach (RWA), reduced insertion angles, and use of perioperative steroids has become widespread and has proven to be effective in preserving the cochlear structure (13)(14)(15). However, the question of how protective these measures are on the vestibule still remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In the 1990s and into this century, the first steps toward "soft surgery" in cochlear implantation began to be implemented (6,11,12). Now the use of soft electrodes, a round window approach (RWA), reduced insertion angles, and use of perioperative steroids has become widespread and has proven to be effective in preserving the cochlear structure (13)(14)(15). However, the question of how protective these measures are on the vestibule still remains unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Many experimental studies in animals have demonstrated that the use of corticosteroids is able to preserve hearing thresholds, increase the survival of hair cells and spiral ganglia, and decrease the formation of new fibrotic tissue within implanted cochlea (20)(21)(22)(23)(24)(25)(26)(27). Clinical studies demonstrate lower impedances and improved preservation of low-frequency residual hearing in patients when corticosteroids are used in CI surgery (28)(29)(30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Results of clinical pilot studies considering pure tone audiometry or electrode impedance measurement showed a slight tendency in favor for local application but only included few patients (32,33). Additionally, a prolonged application after insertion seems to be more effective in suppressing adverse effects than single-shot glucocorticoid application prior to insertion of the cochlear implant electrode (22)(23)(24)(25)(26)(27). In a guinea pig model of insertion trauma, the measurements of inflammatory cytokines in perilymph revealed that suppression of inflammation is most successful when glucocorticoids are applied intracochlearly (26).…”
Section: Introductionmentioning
confidence: 99%
“…It is used in the treatment of diseases such as asthma, arthritis, adrenal insufficiency or chronic obstructive pulmonary disease. In the field of otorhinolaryngology, dexamethasone and other glucocorticoids (e.g., prednisone, methylprednisolone) are used in the treatment of severe and chronic diseases, such as partial deafness, Meniere's disease or autoimmune diseases [16,17].…”
Section: Introductionmentioning
confidence: 99%